2016
DOI: 10.1016/j.jfma.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems vary with medication category and treatment duration in Taiwanese heart failure outpatients receiving case management

Abstract: In Taiwan where the clinical pharmacist system is not well organized, HF outpatients still had a high prevalence of DRPs despite intensive monitoring by nurse case managers. Clinical pharmacists play critical roles in detecting potential DRPs during long-term medication treatment for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
5
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 22 publications
8
28
5
1
Order By: Relevance
“…We have identified at least one DTP in 83.5% of study participants, which was in line to other studies [ 21 , 23 , 27 – 29 ]. The mean number of DTPs per patient was 2.60, which was lower than the mean reported in Taiwan, 5.90 DTPs per patient [ 30 ], but higher than that of Spanish study, 1.5 DTP/patient [ 21 ]. This might variation might be due to the differences in a study design, clinical characteristics, population demographics, medication therapy used and methods of DTP identification and classification.…”
Section: Discussionmentioning
confidence: 61%
“…We have identified at least one DTP in 83.5% of study participants, which was in line to other studies [ 21 , 23 , 27 – 29 ]. The mean number of DTPs per patient was 2.60, which was lower than the mean reported in Taiwan, 5.90 DTPs per patient [ 30 ], but higher than that of Spanish study, 1.5 DTP/patient [ 21 ]. This might variation might be due to the differences in a study design, clinical characteristics, population demographics, medication therapy used and methods of DTP identification and classification.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, it was recommended that clinical pharmacists could provide pharmaceutical care for ambulatory patients receiving long-term pharmacotherapy. 23 In our study, condition undertreated was the most common DRP subtype that was identified in patient interviews. A study by Tulner et al also reported that under-treatment usually occurred in elderly patients, with nearly one-third of them identified as being untreated.…”
Section: Discussionmentioning
confidence: 75%
“…When inconsistency existed, a third pharmacist would re-investigate and re-classify. If results remained to be inconsistent, a consensus was reached through discussion [17].…”
Section: Pcne-drp Classificationmentioning
confidence: 99%